SARS‐CoV‐2 and Mitochondrial Proteins in Neural‐Derived Exosomes of COVID‐19. Issue 6 (30th March 2022) - Peluso, Michael J.; Deeks, Steven G.; Mustapic, Maja; Kapogiannis, Dimitrios; Henrich, Timothy J.; Lu, Scott; Goldberg, Sarah A.; Hoh, Rebecca; Chen, Jessica Y.; Martinez, Enrique O.; Kelly, J. Daniel; Martin, Jeffrey N.; et al.
Abstract : Objective: As SARS‐CoV‐2 is known to invade neural cell mitochondria, a plasma system for quantifying central nervous system proteins in living humans was used to investigate neuropathogenic mechanisms of long‐COVID‐19. Methods: SARS‐CoV‐2 proteins and mitochondrial proteins (MPs) in enriched plasma neuron‐derived extracellular vesicles (NDEVs) and astrocyte‐derived EVs (ADEVs) were quantified in resolved acute COVID‐19 without post‐acute sequelae of SARS‐CoV‐2 (PASC), PASC without neuropsychiatric manifestations (NP), PASC with NP and healthy controls. Results: NDEV and ADEV mean levels of SARS‐CoV‐2 S1 and nucleocapsid (N) proteins were higher in all PASC sub‐groups than controls, but only N levels were higher in PASC with than without NP. Exosome marker CD81‐normalized NDEV mean levels of subunit 6 of MP respiratory chain complex I and subunit 10 of complex III, and neuroprotective MPs Humanin and mitochondrial open‐reading frame of the 12S rRNA‐c (MOTS‐c) all were decreased significantly in PASC with NP but not in PASC without NP relative to controls. NDEV levels of MPs voltage‐dependent anion‐selective channel protein 1 (VDAC1) and N‐methyl‐D‐aspartate receptor 1 (NMDAR1) were decreased in PASC without and with NP, whereas those of calcium channel MPs mitochondrial calcium uniporter (MCU), sodium/calcium exchanger (NCLX) and leucine zipper EF‐hand containing transmembrane 1 protein (LETM1) were decreased only in PASC with NP. ADEV levels of MCU and NCLX only were increased in PASC without and with NP. Interpretation: Abnormal NDEV and ADEV levels of SARS‐CoV‐2 N and S1 protein and MPs correlate with NP and may be biomarkers for long‐COVID prognostics and therapeutic trials. ANN NEUROL 2022;91:772–781 Abstract :